A Large Cardiac Hydatid Cyst in the Interventricular Septum with Hepatic Involvement in Young Male: A Rare Case Presentation - Amit Goyal; Ashish Bansal (Research in Cardiovascular Medicine, 2024)
Hydatid disease is a parasitic infestation caused by larvae of the Echinococcus tapeworm. It mainly affects the liver and lungs. Cardiac hydatid cyst is uncommon and involvement of the interventricular septum is even rarer. It may lead to various complications because of rupture and embolization. We report the case of a 24-year-old man who was diagnosed to have a large interventricular hydatid cyst associated with cysts in the liver which mimics like acute coronary syndrome. This case is of particular interest because of the rarity of septal localization of a hydatid cyst, and concurrent involvement of the liver and cardiac is uncommon.